2022
DOI: 10.1002/smll.202203200
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Assembly of Flexible Biopolymer Polyphosphate‐Manganese into Nanosheets

Abstract: Polyphosphate (polyP) is one of the most compact inorganic polyanionic biopolymers that participates in various physiological processes. However, the development of polyP‐based nanomaterials is still in its infancy. Here, biocompatible polyphosphate‐manganese nanosheets are designed and synthesized by a hierarchical assembly strategy. The thickness and the lateral size of the resulting polyP‐Mn nanosheets (PMNSs) are 5 nm and 120–130 nm, respectively. Molecular dynamics simulations suggested that the polyP‐hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
0
0
Order By: Relevance
“…The negatively charged multifunctional polymer contains phosphoanhydride bonds that are isoenergetic to those found in ATP 23 . Previous research has demonstrated that the structure of polyP can modified and programmed to perform specific functions at the nanoscale in bone repair [24][25][26][27] , clotting [28][29][30][31][32] , and immunotherapy 33 . Additionally, certain polyP-based nanostructures exhibit close similarities to natural proteins in both morphology and function.…”
mentioning
confidence: 99%
“…The negatively charged multifunctional polymer contains phosphoanhydride bonds that are isoenergetic to those found in ATP 23 . Previous research has demonstrated that the structure of polyP can modified and programmed to perform specific functions at the nanoscale in bone repair [24][25][26][27] , clotting [28][29][30][31][32] , and immunotherapy 33 . Additionally, certain polyP-based nanostructures exhibit close similarities to natural proteins in both morphology and function.…”
mentioning
confidence: 99%